PENGARUH INTEGRITAS, OBYEKTIVITAS, KERAHASIAAN, KOMPETENSI, DAN KOMITMEN TERHADAP KINERJA AUDITOR PADA KANTOR PERWAKILAN BADAN PENGAWASAN KEUANGAN DAN PEMBANGUNAN (BPKP) PROVINSI SULAWESI TENGAH - Baisary, Rizky Pasca (Katalogis, 2013)
This research aims to know and analyze simultaneous effects of integrity, objectivity, confidentiality, competency, and commitment on auditor’s performance at Board of Development and Financial Audit (BPKP), Representative Office of Central Sulawesi Province. Data of this research concist of primary and secondary data that have been collected using means of questionnaire, interviews, and documentation. Multiple linear regression has been used as analysis method in this research. The results show that integrity, objectivity, confidentiality, competency, and commitment perform simultaneous effects on auditor’s performance at Board of Development and Financial Audit (BPKP), Representative Office of Central Sulawesi Province. This is indicated by the value of adjusted R square 0.851 which means that 85.1% auditor’s performance has been affected by integrity, objectivity, confidentiality, competency, and commitment. Based on partial test result, competency is the most dominant variable influencing auditor’s performance at Board of Development and Financial Audit (BPKP), Representative Office of Central Sulawesi Province i.e. 28%.